The Role of Road Hierarchization in Development of Transport Infrastructure in Urban Areas and Its Links to Urbanism - Suk, Antonín; Ledvinová, Michaela (Kaunas University of Technology, 2022)
The hierarchization of roads plays a crucial role in the development of transport infrastructure in urban areas. Roads in urban areas can be described in a dualistic manner: as conductors of traffic (transport-engineering aspect) and as structures mirroring functions of the city (urbanistic aspect). However, few methods explore this dualistic characteristic, and so the hierarchization of roads is usually based solely (mainly) on the transport-engineering aspect. This paper discusses the importance of the dualistic characteristic and introduces a hierarchization method based on both aspects. The results of this study could contribute to our practical and intuitive understanding of the effects of transport on the development of cities and on other topics related to transport/urbanism.
Role hierarchizace komunikací v rozvoji dopravní infrastruktury v městských oblastech a její vazby na urbanismus
Keywords: transport-engineering aspect; urbanistic aspect; hierarchization methods; transport infrastructure; dopravně-inženýrské hledisko; urbanistické hledisko; hierarchizační metody; dopravní infrastruktura